Contingent valuation of nonmarket benefits in project economic analysis a guide to good practice - Sajise, Asa Jose; Samson, Jindra Nuella G.; Quiao, Lotis; Sibal, Jasmin; Raitzer, David A.; Harder, Dieldre (Asian Development Bank, 2021)
Explains how to measure people's willingness to pay for goods and services, such as improved air quality, that are not traded in a market. This guide aims to help improve the assessment of potential investment projects.